The potential of wetlands and barrier islands as a coastal defense in mitigating the storm surge - Gupta, Aditya; Bilskie, Matthew V.; Woodson, C. Brock (Frontiers in Ecology and Evolution, 2025)
A critical aspect of coastal protection is the role of barrier islands and wetlands in mitigating storm surges. However, the level of protection offered by these natural features can vary based on their geographical characteristics and the storms they face. This study focuses on quantifying the attenuation capacity of the Apalachicola Bay barrier island and coastal wetland system using a novel approach that delineates watersheds to calculate localized water elevation attenuation rates, incorporating spatially varying bed roughness and complex channel-marsh networks. We simulated storm surge dynamics using the ADvanced CIRCulation (ADCIRC) model under multiple configurations, including entire barrier island presence, selective island removal, the absence of all islands, and scenarios with and without marsh vegetation. The study introduces an attenuation rate function based on the prediction factor that improves surge attenuation modeling by integrating real-world scenarios with idealized theoretical functions. Additionally, we derive a theoretical maximum attenuation rate curve to calculate the highest achievable rate of storm surge reduction in Apalachicola Bay, providing a benchmark for the landscape’s full attenuation potential. The findings of this study underscore the importance of integrating wetlands and barrier islands into coastal protection strategies. Insights from this study can guide restoration efforts, particularly in the context of barrier islands and marshlands, to enhance resilience against increasing storm surge threats.